Peran Komunikasi Keluarga dalam Interaksi Wisata pada Film Keluarga Cemara - Naswa Fajriah; Rania Azelia Afra; Nadia Cesya Aurelia; Laudi Sinta Bela; Arsih Amalia Chandra Permata; Wiyata Wiyata (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
This study examines how verbal and nonverbal cues in the movie represent interpersonal communication among family members using a qualitative-descriptive methodology, semiotic analysis and Lasswel theory. The results show that openness, empathy, collaborative decision-making, and togetherness—all essential components of good family communication are major themes that influence the characters' ability to bounce back from both emotional and financial adversity. Abah is a crucial character who represents accountability, love, and tenacity. She also illustrates how communication may be used to fortify family ties in times of adversity. According to the study's findings, family communication is essential for settling disputes and building social support within the family in addition to preserving emotional intimacy.